Indirect effects of paediatric conjugate vaccines on invasive pneumococcal disease in older adults. (September 2019) - ,; Ciruela, P.; Izquierdo, C.; Broner, S.; Hernández, S.; Jané, M.; Muñoz-Almagro, C.; Esteva, C.; de Sevilla, M.F.; Henares, D.; Pallarés, R.; Ardanuy, C.; et al.
Highlights: Overall invasive pneumococcal disease (IPD) decreased by 19% in older adults due to the impact of childhood 13-valent pneumococcal conjugate vaccine (PCV13) vaccination. IPD caused by non-PCV13 serotypes increased by 36% in older adults. During 2014–2016, the IPD mortality rate was 17.5%. The IPD mortality risk was found to be associated with older age, clinical form, high-risk conditions, and PCV13 serotypes. Improving PCV13 vaccination coverage in children and 23-valent pneumococcal polysaccharide vaccine (PPV23) in adults will decrease the incidence and severity of IPD in older adults. Abstract: Objectives: The aim of this study was to assess the indirect effect of paediatric 13-valent pneumococcal conjugate vaccine (PCV13) vaccination on people ≥65 years of age with invasive pneumococcal disease (IPD) in Catalonia and to determine factors predictive of mortality. Methods: During 2014–2016, 1285 IPD cases were reported to the Public Health Agency of Catalonia. The indirect effect of paediatric PCV13 vaccination was calculated by comparing the incidence rate (IR) in 2016 (PCV13 year) with that in 2009 (pre-PCV13). Predictors of mortality were determined using multivariate logistic regression. Results: Comparing 2016 and 2009, IPD decreased by 19% (IR 40.1 and 32.5 per 100 000 person-years, respectively). PCV13 serotypes decreased by 57% (IR 23.7 and 10.1), while non-PCV13 serotypes increased by 36% (IR 16.4 and 22.4). During 2014–2016, the mortality rate was 17.5%, and mortality was associated with age ≥85 years (adjusted odds ratio (aOR) 2.91, 95% confidence interval (CI) 1.89, 4.48), meningitis (aOR 2.29, 95% CI 1.25, 4.19), non-focal bacteraemia (aOR 3.73, 95% CI 2.00, 6.94), and ≥1 high-risk condition (aOR 1.89, 95% CI 1.08, 3.32). PPV23non13 serotypes were associated with lower mortality than PCV13 serotypes (aOR 0.54, 95% CI 0.34, 0.86). Conclusions: The incidence of IPD in people ≥65 years of age decreased after the introduction of paediatric PCV13, and this was due to a reduction in PCV13 serotypes, although an increase in non-PCV13 serotypes was observed. Mortality was associated with age, meningitis, non-focal bacteraemia, ≥1 high-risk condition, and PCV13 serotypes.